- #1

- 99

- 0

**chain rule agian - check my work plz**

w = -xy-5yz+3xz, x = st, y = exp(st), z = t^2

dw/ds(5,-2) = ________________________

here's what i did:

dw/ds = dw/dx*dx/ds + dw/dy*dy/ds + dw/dz*dz/ds

dw/ds = (3z-y)*(t) + (-x-5z)(exp(st)*t) + (3x-5y)(0)

plug in x,y and z.....

dw/ds = (3(t^2)-(exp(st)))*(t) + (-(st)-5(t^2))(exp(st)*t) + (3(st)-5(exp(st)))(0)

now plug in s=5 and t=-2.....

dw/ds = (3(5^2)-(exp(5*-2)))*(5) + (-(5*-2)-5(5^2))(exp(5*-2)*-2) + (3(5*-2)-5(exp(5*-2)))(0) = 375.01 which is incorrect. i checked my work three times and i cant find the problem, which means im doing something wrong